Penerapan Green Accounting Sebelum dan Sesudah Penetapan Virus Covid-19 sebagai Bencana Nasional - Sarlina Sari (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study aims to test the application of green accounting before Covid-19   was designated as a national disaster and after Covid-19   was designated as a national disaster in Cement Sub-sector companies. Green accounting in this study is measured by two variables, namely environmental performance based on PROPER indicators and environmental disclosures obtained based on data obtained from company sustainability reports with GRI Standards 2018 disclosure indicators. This study uses an event study to analyze changes in the application of green accounting that occur in companies. from day to day with an event period of 1 year before and after Covid-19   is designated as a national disaster. The results show that not all companies are registered in the green PROPER category, both before Covid-19   was declared a national disaster (in 2019), and after Covid-19   was declared a national disaster (in 2020). However, all companies, both before Covid-19   was declared a national disaster (in 2019), and after Covid-19   was declared a national disaster (in 2020) had a level of disclosure in accordance with the 2018 GRI Standard indicators, although the percentage of disclosure decreased in 2020. With the results of this study, company is hoped that they will pay more attention to the environment, in the future they can at least get a blue rating in PROPER if it is not possible to get a green or gold rating. Keywords: green accounting, environmental performance, environmental disclosure, Covid-19